Literatura e luz: iluminação elétrica, teatro e o filme expressionista - Korfmann, Michael (Contingentia, 2010)
This article discusses the influence of electric illumination on theatre and the so called expressionist film. It starts with a short historical overview and will then argue that the only film with a narrative as well as a visual design in expressionist tradition is From Morn to Midnight, based on a play written in 1912 by Georg Kaiser and released in same year (1920) as its legend counterpart The Cabinet of Caligari. But different then Caligari or many other famous German silent movies from the 1920s it is not located in a romantic shadow world, syntactically created by lightning effects, but renounces the dark and spooky irrational in favor of an urban environment in the early twentieth century: a story of money, erotic seduction, escapist fantasies, eccentric bohemian life, crime and rapid alteration of scenes.